Minutes of General Council (extract)
039-0039-001 G.C Minutes 23rd March 1938 147. BARCELONA BOMBARDMENTS. Telegram was received from Miss Jacobsen of the Scottish Ambulance Unit in Spain, dated 22nd March, 1938, regarding the Barcelona bombardments, and asking the Council to arrange for the reception in Britain of some 2,000 women and children. IT WAS DECIDED that the Secretary write a suitable letter, pointing out that the Council's resources were not adequate to meet the demand. 292/946/39/39